2022
DOI: 10.3389/fphar.2022.830791
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and Pharmacokinetics of HSK3486, a Novel 2,6-Disubstituted Phenol Derivative as a General Anesthetic

Abstract: Background: The purpose of this study was to characterize the novel sedative/hypnotic agent HSK3486, a 2,6-disubstituted alkylphenol analogue.Methods: The mechanism of action of HSK3486 was studied in competitive binding assays and whole-cell patch clamp assays. HSK3486 was administered by bolus intravenous injection to dogs and rats, and the loss of righting reflex as well as effects on the cardiovascular and respiratory systems were assessed. The in vitro metabolism of HSK3486 was analyzed by CYP450 genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…However, propofol has unavoidable limitations, such as a narrow therapeutic index, injection pain, circulation and respiratory depression, and infusion syndrome ( Hughes et al, 2021 ). The active ingredient of ciprofol is similar to propofol, but it has single R-configured diastereoisomers ( Liao et al, 2022 ). The innovation of this drug lies in the cyclopropyl group, which not only increases the steric effect but also introduces stereoselective effects over their anesthetic properties ( Li et al, 2021 ; Hu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol has unavoidable limitations, such as a narrow therapeutic index, injection pain, circulation and respiratory depression, and infusion syndrome ( Hughes et al, 2021 ). The active ingredient of ciprofol is similar to propofol, but it has single R-configured diastereoisomers ( Liao et al, 2022 ). The innovation of this drug lies in the cyclopropyl group, which not only increases the steric effect but also introduces stereoselective effects over their anesthetic properties ( Li et al, 2021 ; Hu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar to propofol, extensive metabolic clearance to inactive metabolites by UDP-glucuronosyltransferases (UGTs) and CYP enzymes in the liver was considered the major contributor to total body clearance of HSK3486. In vitro studies imply that CYP2B6 is the major CYP enzyme that mediates HSK3486 metabolism [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major circulating metabolite of HSK3486, M4 (79.3%), is a nonhypnotic and non-toxic glucuronidation product that is excreted through urine. Previous in vitro studies imply CYP2B6 is the major CYP enzyme that mediates HSK3486 metabolism [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like propofol, ciprofol is a positive allosteric modulator and direct agonist of the GABA A receptor. Competitive binding assays and whole-cell patch-clamp experiments demonstrated that ciprofol could trigger chloride influx by competitive binding to butylbicyclophosphorothionate and t-butylbicycloorthobenzoate targets in the chloride channels of GABA A receptors [ 19 ]. The influx of chloride can cause hyperpolarization of nerve cell membranes by increasing the intracellular chloride concentration and further activating GABAergic neurons to achieve central nerve inhibition, producing sedative and anesthetic effects.…”
Section: Structural Features and Mechanismsmentioning
confidence: 99%